Media worlds : anthropology on new terrain - Ginsburg, Faye D.; Abu-Lughod, Lila; Larkin, Brian (University of California Press, 2002)
This groundbreaking volume showcases the exciting work emerging from the ethnography of media, a burgeoning new area in anthropology that expands both social theory and ethnographic fieldwork to examine the way media--film, television, video--are used in societies around the globe, often in places that have been off the map of conventional media studies.